THE ESCUINTLA AND LA DEMOCRACIA DEBRIS AVALANCHE DEPOSITS, GUATEMALA: CONSTRAINING THEIR SOURCES - Chesner C.A.; Halsor S.P. (My University, 2006)
The Escuintla and La Democracia debris avalanches are the two largest debris avalanches so far identifi ed in Guatemala, with respective volumes of 9-15 km3 and 2.4-5 km3. Based upon their geographic locations on the Guatemalan coastal plain, both deposits have several possible source volcanoes. The Escuintla debris avalanche could have originated at either the Fuego or Acatenango volcanic complexes, or Agua volcano. Farther to the west, the La Democracia debris avalanche could only have come from the Fuego or Acatenango volcanic complexes. An apparent collapse scar on the east face of the Meseta edifi ce (the northernmost vent of the Fuego volcanic complex) has been attributed to the formation of the Escuintla debris avalanche. A mostly obscured summit collapse scar on Acatenango and an erosional remnant of a debris avalanche deposit near the base of the cone have been linked to the La Democracia debris avalanche. Petrographic and geochemical analyses of lava blocks collected from the Escuintla debris avalanche suggest that a substantial volume of amphibole-bearing dacitic lavas were present at its source volcano. Examination of rocks from the possible source volcanoes indicate that no dacitic lavas or tephras are known to have erupted from the Fuego volcanic complex and that the rocks exposed in the Meseta scarp bear little resemblance to the Escuintla debris avalanche samples. A few dacitic lavas and tephras are known from the Agua volcano, and several dacitic tephras have erupted from Acatenango. Geochemical comparisons of lavas and tephras from these volcanoes with rocks from the Escuintla debris avalanche showed greater similarities than those from Fuego and Meseta. Even though Acatenango is not known to have erupted dacitic lavas, its geochemistry is the most consistent with that of the Escuintla debris avalanche. Lava blocks from the La Democracia debris avalanche are mostly basaltic, although one andesitic sample contains phenocrystic amphibole. Geochemical analyses of Fuego and Meseta lavas overlap with the La Democracia debris avalanche samples; however, no amphibole-bearing rocks are known from Meseta, and Fuego is presumed to be younger than the La Democracia debris avalanche. Compared to the Acatenango rocks, the geochemistry and mineralogy of the La Democracia debris avalanche are quite similar. Furthermore, rocks from the debris avalanche deposit on the fl ank of Acatenango are also consistent with the chemistry of the La Democracia debris avalanche. Thus, Acatenango produced at least one debris avalanche, the La Democracia debris avalanche, and possibly also generated the Escuintla debris avalanche. © 2006 Geological Society of America.
Keywords: ACATENANGO; AGUA; DEBRIS AVALANCHE; FUEGO; GEOCHEMISTRY